The voices of the tale: the storyteller in early Byzantine collective biographies, miracle collections, and collections of edifying tales. (April 2022) - Constantinou, Stavroula; Andreou, Andria
Abstract : This article is a first attempt to approach the figure of the storyteller in three types of early Byzantine tale collections (fourth–seventh centuries): collective biography, miracle collection, and collection of edifying tales. Our approach draws significantly on Walter Benjamin's discussion of the storyteller and Monica Fludernik's work on conversational storytelling. Our analysis has a twofold purpose: first, to revise the impression that the storyteller is a canonical force that possesses the same characteristics in every single tale; second, to suggest that the storyteller is an inherent feature of short hagiographical narratives.